Vaccination coverage against COVID-19 among adults of rural field practice area, tertiary-care hospital: cross-sectional study - Reddy, Kamuni Madhuri; Pasha, M. A. M.; Fatima, Afsar (International Journal Of Community Medicine And Public Health, 2023)
Background: As the spread of COVID-19 pandemic, lockdown has been implemented and as a preventive measure to reduce the occurrence of disease vaccination has been conducted throughout the country level. Methods: A Community based Cross Sectional study was conducted during September 2022 to October 2022 (2months) in RHTC field practice area of Santhiram Medical College, nandyal among adults (25-45) years of age group by convenient sampling method with sample size 300, study tool was pre-designed, semi structured questionnaire. Data was collected by interview method and analysed by SPSS 22 version. Ethics committee clearance was obtained before conducting the study. Results: In this study population, (48%) completed 3 doses of COVID vaccine with booster dose, (48.3%) got vaccinated for 2 doses and (3.7%) are vaccinated for 1st dose and (15%) of them got COVID infection after vaccination. Conclusions: Out of 300 participants 53% were males and 47% were females, 4% with one dose, 48% with two doses and 48% with two doses with booster dose of vaccination, about 36% had comorbidities. About 35% vaccinated by covaxin and 65% is with covishield vaccine, in which 9% had COVID infection after vaccination. Therefore, along with regular monitoring and surveillance, health education regarding the advantages of vaccination to the people can improve the vaccination status in rural area.